2009
DOI: 10.1007/978-3-642-04268-3_72
|View full text |Cite
|
Sign up to set email alerts
|

A Meta Registration Framework for Lesion Matching

Abstract: A variety of pixel and feature based methods have been proposed for registering multiple views of anatomy visible in studies obtained using diagnostic, minimally invasive imaging. A given registration method may outperform another depending on anatomical variations, imaging conditions, and imaging sensor performance, and it is often difficult a priori to determine the best registration method for a particular application. To address this problem, we propose a registration framework that pools the results of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Several newly published articles supported this consensus process, or the so-called meta-registration process, such as [72], [116]–[118]. Doshi et al recently combined ANTs and DRAMMS in a multi-atlas labeling framework, resulting in a top-performing method in a MICCAI segmentation challenge [72].…”
Section: Discussionmentioning
confidence: 99%
“…Several newly published articles supported this consensus process, or the so-called meta-registration process, such as [72], [116]–[118]. Doshi et al recently combined ANTs and DRAMMS in a multi-atlas labeling framework, resulting in a top-performing method in a MICCAI segmentation challenge [72].…”
Section: Discussionmentioning
confidence: 99%
“…Such modifications could further aid the registration to focus on ROI, and could largely reduce the negative impacts from structures that are not of interest to the specific application. Finally, we could also explore methodologies to form a consensus mechanism, where multiple registration methods can complement each other toward more accurately capturing voxelwise volumetric changes [e.g., ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative evaluations have shown that it can reduce the frame number down to less than 10% with almost no loss of information. In our future work, we plan to extend the semantically organized epitome for WCE image registration [13].…”
Section: Resultsmentioning
confidence: 99%